The Prominence And Contribution Of Abu Hassan Ali Al-Nadwi On Strengthening The Spread Of Da’wah In Muslim World, 1913-1999 - Nur Farihah Ahmad; Mashitah Sulaiman (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceedings Of The International Conference On Da’wah And Islamic Management (IC-DAIM 2021) “Humane Leadership and Da’wah For Sustainable Future of Ummah” 26-27 October 2021 Organized by: Da’wah and Islamic Management Program, Faculty of Leadership and Management, USIM